Administration of the deceased’s estates an analysis to the effect of nomination - Drs Nasrul, Muhammad Amrullah; Mohd Salim, Wan Noraini; Abdul Hak, Nora; Halim, Akmal Hidayah; Abdul Manab, Siti Nuramani (©2018 Published by the Future Academy, 2018)
In the administration of estate, the asset related to nomination is governed under the nomination rules set by the different authorities, which gave rise to several nomination effects. Some of these nomination prevents the asset to be distributed to the rests of beneficiaries, other than the nominee. Other nomination effect grants the authority to the nominee as an administrator to that particular asset, without considering the capacity and ability of such nominee in distributing the asset. While the purpose of nomination is to ensure a quick and smooth process in extracting the deceased’s asset, the differences in the nomination effect tend to cause confusion, leading to disputes between the nominee and the beneficiaries in claiming the ownership of the estate. This paper discusses the position of the asset under nomination through the analysis of provisions under the Islamic Financial Services Act 2013 in relation to the administration and the distribution of the deceased’s estate. The research is conducted through the means of a library-based method which utilises written materials in several sources including journal articles, statutes, textbooks and cases. The finding in this study indicates that the lack of control by the institutions over the nomination process has led to the adverse implication involving the disputes between the parties. It is therefore suggested that the lawmaker needs to amend the nomination rules in order to harmonise the rights of the nominee and the beneficiaries of the deceased’s estates respectively.